2018
DOI: 10.1038/s41467-018-04447-7
|View full text |Cite
|
Sign up to set email alerts
|

Integrin beta3 regulates clonality and fate of smooth muscle-derived atherosclerotic plaque cells

Abstract: Smooth muscle cells (SMCs) play a key role in atherogenesis. However, mechanisms regulating expansion and fate of pre-existing SMCs in atherosclerotic plaques remain poorly defined. Here we show that multiple SMC progenitors mix to form the aorta during development. In contrast, during atherogenesis, a single SMC gives rise to the smooth muscle-derived cells that initially coat the cap of atherosclerotic plaques. Subsequently, highly proliferative cap cells invade the plaque core, comprising the majority of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
229
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 162 publications
(241 citation statements)
references
References 48 publications
11
229
1
Order By: Relevance
“…Atherosclerotic lesions grow via recruitment of bone marrow-derived monocytes and local proliferation of lesional macrophages and VSMCs (14)(15)(16). This study using MIMS identified higher rates of proliferation in foam cells as compared with prior reports (15,17).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Atherosclerotic lesions grow via recruitment of bone marrow-derived monocytes and local proliferation of lesional macrophages and VSMCs (14)(15)(16). This study using MIMS identified higher rates of proliferation in foam cells as compared with prior reports (15,17).…”
Section: Discussionmentioning
confidence: 52%
“…In contrast to foam cells, medial VSMC proliferation occurred in a more discrete subpopulation of cells. Whether these 15 N-positive VSMCs will preferentially contribute to plaque growth is the subject of ongoing work coupling lineage-tracing approaches with MIMS (14,19). However, we did detect lipid-laden VSMCs directly underlying the intima (Figure 3), indicative of foam cell-like changes.…”
Section: Discussionmentioning
confidence: 82%
“…Variance concerning the expression of CD140b could only be observed when measured as surface protein, not in the gene expression analysis. This discrepancy might emerge from regulated trafficking of CD140b 47 that seems to be of relevance during SMC recruitment to the fibrous cap 14,48 and further illustrates SMC plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, VSMCs migrate and proliferate to the surrounding of the necrotic core and play an important role in creating a fibrous cap that stabilizes the atherosclerotic plaque [3,4].Moreover, VSMCs can differentiate into many other cell types found in the plaque core, suggesting that these cells might participate in multiple processes underlying atherosclerotic plaque stability [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%